Cutaneous reactions to targeted therapies in children with CNS tumors: A cross‐sectional study. Issue 6 (28th February 2019) - Song, Hannah; Zhong, Connie S.; Kieran, Mark W.; Chi, Susan N.; Wright, Karen D.; Huang, Jennifer T.
Abstract: Background: MAPK (RAS–RAF–MEK–ERK–MAP) and mTOR inhibitors are novel treatments for pediatric central nervous system (CNS) tumors. The literature on common cutaneous adverse reactions to these therapies is sparse in the pediatric population. The aim of this study was to describe common cutaneous adverse reactions to BRAF, MEK, and mTOR inhibitors in children with CNS tumors. Methods: In this cross‐sectional study, patients younger than 21 years of age receiving BRAF, MEK, and mTOR inhibitor monotherapy for a CNS tumor were enrolled over a one‐year period. Full body skin examination, photographs of dermatologic findings, and initial treatment recommendations were included at the initial visit, and follow‐up skin examinations were recommended every three months. Results: Twenty‐two patients were enrolled in the study. Fifty percent (11/22) received trametinib, a MEK inhibitor, 27.3% (6/22) received dabrafenib, a BRAF inhibitor, and 22.7% (5/22) received everolimus, an mTOR inhibitor. Median age at visit was 11 years (range, 3–19). Median time from treatment initiation to skin examination was 4.5 months (range, 0–43). Ninety‐six percent (21/22) of all patients had at least one skin reaction. The most common reactions across treatment groups included follicular/acneiform eruptions and xerosis. Two patients on MEK inhibitors and one patient on a BRAF inhibitor required therapy cessation due to severe cutaneous reactions. Conclusions: Cutaneous reactions to targeted anticancer therapy in children are common, treatable, and rarely require drug dose reduction or discontinuation. Routine surveillance and early intervention may improve quality of life and facilitate continuation of life‐saving therapy.